Statistics for managers using Microsoft Excel - Levine, David M.; Berenson, Mark L.; Stephan, David (Upper Saddle River, N.J. : Prentice Hall, 1999)
Introduction and data collection. Using Microsoft Excel for statistical analysis. Presenting data in tables and charts. Summarizing and describing numerical data. Basic probability and discrete probability distributions. Decision making. The normal distribution and sampling distributions. Confidence interval estimation...
Keywords: Microsoft Excel; Statistical methods; Microsoft Excel (Computer file); Commercial statistics -- Computer programs; Commercial statistics; Management -- Statistical methods; Electronic spreadsheets; Management -- Statistical methods -- Computer programs